2023
DOI: 10.3390/ijerph20053851
|View full text |Cite
|
Sign up to set email alerts
|

The Experience of COVID-19 in a Sample of Gynecological Cancer Patients Undergoing Chemotherapy: A Focus on the Psychological Implications

Abstract: Cancer patients are at an increased risk of developing severe consequences due to the COVID-19 infection. However, psychological outcomes in this population have been overlooked in the literature. The present study aims to identify significant psychological differences between gynecological cancer patients undergoing chemotherapy before and during the pandemic. Additionally, we explore the correlations between COVID-19-related concerns and anxiety, depression, distress, and quality of life levels. Forty-two pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 55 publications
0
1
0
Order By: Relevance
“…At the same time, the SARS-CoV-2 infection can cause physical discomfort. Studies have confirmed that this comorbidity further affects the quality of life (QOL) and psychological state of other patients with cancer; however, whether it alters the QOL of patients with breast cancer has not been reported [ 9 10 11 ]. During the period of change in our hygienic and epidemiologic policies, a large number of patients treated with NAC became infected with SARS-CoV-2, and this study addresses this issue.…”
Section: Introductionmentioning
confidence: 99%
“…At the same time, the SARS-CoV-2 infection can cause physical discomfort. Studies have confirmed that this comorbidity further affects the quality of life (QOL) and psychological state of other patients with cancer; however, whether it alters the QOL of patients with breast cancer has not been reported [ 9 10 11 ]. During the period of change in our hygienic and epidemiologic policies, a large number of patients treated with NAC became infected with SARS-CoV-2, and this study addresses this issue.…”
Section: Introductionmentioning
confidence: 99%